Suksesi mangrove di kawasan restorasi Taman Nasional Sembilang Sumatera Selatan - Sarno Sarno; Harmida Harmida; Nita Aminasih; Hanifa Marisa (Sriwijaya Bioscientia, 2020)
Mangrove conditions in the region under pressure and degradation from year to year. The main cause of mangrove destruction in the Sembilang National Park (SNP) is cultivation or manufacture of fish ponds, especially in the Peninsula Banyuasin South Sumatra. The activities of these ponds have resulted in the degradation of mangrove, especially in greenbelt. The destruction of mangrove areas causes a decrease in the quality and extent of mangrove areas which result in the degradation of a variety of important functions. Damage to mangroves occur both at the regional, national and even up to the global level. The purpose of this study is to know the process of natural mangrove revegetation on former ponds. The composition of the type of vegetation that grows in the area of the former ponds in South Sumatra region SNP restoration consists of four species: Avicennia marina (Forssk.) Vierh., Avicennia alba Blume, Rhizophora mucronata Lam., and Portulaca villosa. The most dominant species of mangrove revegetation of former pond in SNP is A. marina.